Augmented Reality as Education by Using Animal Announcer Based on Android Application - Ledyana; Arif Arizal; R Dimas Adityo (JEECS (Journal of Electrical Engineering and Computer Sciences), 2017)
The method used in making applications Introduction This animal is the study of literature, experiment, samplingand interviews. Making animal begins with collecting data that will be created as a model using Blender softwareAugmented Reality application design using Unity software by designing a marker made using Photoshop, soundedited using Adobe Audition and animal models that have been made. The features available in this app are severaltypes of animals that are displayed in 3D with sound and animation using Augmented Reality technology. Results oftesting applications Introduction Pets can run on a variety of Android mobile devices. The normal distance that canbe detected by the camera is 6cm up to 4m with marker size 20 x 22cm. Based on that test the accuracy of readingthe average marker is 00:12 seconds every marker. Accuracy of reading marker is also given light. The lighter themarker the clearer and faster the marker. There are still many shortcomings that can be developed, such as animalsreproduce 3D objects and create animations that better, so that the application more attractive, interactive, and easyto understand.